2021
DOI: 10.3389/fmolb.2021.762673
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotective Effects and Molecular Mechanism of Berberine

Abstract: Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide. Atherosclerosis is the main pathological basis of cardiovascular diseases and it is closely associated with hyperlipidemia, endothelial injury, macrophage-derived foam cells formation, proliferation and migration of vascular smooth muscle cells (VSMCs), platelet aggregation, and altered gut microbiota. Various symptomatic treatments, that are currently used to inhibit atherosclerosis, need to be administered in long term and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 105 publications
(118 reference statements)
1
2
0
Order By: Relevance
“…Consistent with previous investigations, our results showed that BBR can inhibit inflammatory-associated mediators’ expression by dampening the JAK2/STAT3 signaling activation in cats with DSS-induced colitis. The present study results demonstrate that BBR improves the symptoms and inflammation in DSS-induced cats, which lays the foundation for further investigation of the effects of BBR on smooth muscle motility-related phosphorylation ( 50 ). The phosphorylation of MLC regulates smooth muscle contractility.…”
Section: Discussionsupporting
confidence: 58%
“…Consistent with previous investigations, our results showed that BBR can inhibit inflammatory-associated mediators’ expression by dampening the JAK2/STAT3 signaling activation in cats with DSS-induced colitis. The present study results demonstrate that BBR improves the symptoms and inflammation in DSS-induced cats, which lays the foundation for further investigation of the effects of BBR on smooth muscle motility-related phosphorylation ( 50 ). The phosphorylation of MLC regulates smooth muscle contractility.…”
Section: Discussionsupporting
confidence: 58%
“…Several risk factors, including obesity, diabetes, asthma, age, genetic history, and metabolic syndrome have been considered for CVDs. In 2016, the mortality rate associated with CVDs was nearly 17.6 million worldwide, which increased to 17.9 million in 2020 (Pourbagher‐Shahri et al, 2021; Xing et al, 2021). Therefore, many efforts have been made to identify the pathophysiology of these diseases and to inhibit their progression and death.…”
Section: Berberine and The Pi3k/akt Pathway In Cardiovascular Diseasesmentioning
confidence: 99%
“… 9 Some studies have shown a beneficial effect of berberine for AS by lowering serum lipid levels, improving endothelial dysfunction, inhibiting macrophage inflammation and foam cell formation, activating macrophage autophagy, and regulating the proliferation and migration of vascular smooth muscle cells (VSMCs). 10 Wu et al found that berberine improved serum lipids and systemic inflammation in apolipoprotein E (ApoE) -/- mice with AS induced by high-fat diet. 11 Oxidized low density lipoprotein (ox-LDL) within plaques is regarded as playing a key role in AS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%